Large‐scale analysis of viral nucleic acid spectrum in temporal lobe epilepsy biopsies - Esposito, Laura; Drexler, Jan F.; Braganza, Oliver; Doberentz, Elke; Grote, Alexander; Widman, Guido; Drosten, Christian; Eis‐Hübinger, Anna M.; Schoch, Susanne; Elger, Christian E.; Becker, Albert J.; Niehusmann, Pitt (Epilepsia (Copenhagen), 2015)
Summary Objective Chronic inflammatory processes are important promotors of temporal lobe epilepsy (TLE) development. Based on human herpesvirus 6 (HHV‐6) DNA detection in brain tissue from patients with TLE, an association of persistent viral infection with TLE has been discussed. Individual studies reported increased HHV‐6 DNA in patients with clinical signs of previous inflammatory brain reaction, that is, febrile seizures or meningoencephalitis. However, detection rates vary considerably between different studies. Here we performed a large‐scale analysis of viral DNA/RNA spectrum in high‐quality TLE biopsies. In addition to all Herpesviridae, we addressed potentially relevant neurotropic RNA viruses. Methods DNA and RNA were extracted from 346 fresh‐frozen tissue samples removed by epilepsy surgery. Real‐time polymerase chain reaction (PCR) and nested PCR were performed for Herpesviridae and RNA viruses, respectively. Clinical data were analyzed for earlier signs of inflammatory brain reactions. Fresh‐frozen hippocampal tissue samples from patients without chronic central nervous system (CNS) disease served as controls (n = 62). Seven previous PCR studies with overall 178 TLE patients were additionally analyzed regarding a correlation of clinical parameters and HHV‐6 detection. Results PCR revealed HHV‐6B DNA in 34 specimens (9.8%) from TLE patients. HHV‐6B DNA was also present in eight control samples (12.9%; p > 0.05), but showed a lower virus concentration (p < 0.001). Other herpesviruses and RNA viruses were virtually absent. In patients with clinical signs of previous brain inflammation, HHV‐6B DNA was observed in 15.0%, whereas only 6.3% of the samples from patients without febrile seizures or meningoencephalitis were positive for HHV‐6B DNA (p < 0.05). A meta‐analysis of the eight HHV‐6 PCR studies revealed similar results. Significance This biopsy‐based study shows no differences in frequency of HHV‐6B DNA detection between TLE patients and controls. These results do not support the hypothesis of a persistent HHV‐6B infection as a major pathogenetic factor in TLE. However, the higher virus load in TLE patients and the increased detection rate of HHV‐6B DNA in patients with previous inflammatory brain reactions require further investigations.